ANALISIS FAKTOR PENYEBAB MENURUNNYA MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS IX SMP - Sartika, Mutia; Imran, Imran; Ramadhan, Iwan; Ulfa, Maria; Okianna, Okianna (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This study aims to obtain an overview and information about the factors causing the decline in learning motivation among 9th-grade students at SMP Negeri 17 Satap Sungai Kakap, Kubu Raya Regency. The approach used in this research is qualitative with a descriptive method. The data sources for this research are 9th-grade students at SMP Negeri 17 Satap Sungai Kakap, Kubu Raya Regency, class teachers, and parents of students. The data collection techniques used in this study include interviews, observations, and documentation. The results of this research indicate that the factors causing the decline in learning motivation among 9th-grade students at SMP Negeri 17 Satap Sungai Kakap, Kubu Raya Regency are based on internal factors, particularly the lack of interest in learning, laziness in studying, feeling sleepy in class, being preoccupied and not paying attention to the teacher. External factors include the students' family environment, where working parents lack the desire for further education, a lack of motivation and attention from parents, as well as the teaching style of the teachers, who use lecture-based methods that make students bored and uninterested in learning. Overall, this research provides an overview of the factors causing the decline in learning motivation among students, which include interest, family environment, and teaching style